The Experiences of Mental Health Professionals Supporting Forced Migrants: A Qualitative Systematic Review - Tynewydd, Iona; North, Sophie; Rushworth, Imogen (Refuge, 2020)
Many forced migrants experience trauma in pre-migration, journeying, and post-migration phases of flight. Therefore appropriate mental health provision is required. Whilst previous reviews have explored the experiences of health-care staff in supporting forced migrants, no review was found that focused solely on the experiences of mental health professionals. This qualitative thematic synthesis integrates the findings from ten qualitative studies and identifies analytical constructs that encompass the challenges and facilitators for mental health professionals. Findings will inform how services can be developed to best support staff and enable the provision of high-quality mental health care for this potentially vulnerable population.